Bricolage and MSEs in emerging economies. (May 2021) - Simba, Amon; Ojong, Nathanael; Kuk, George
This conceptual paper focuses on bricolage and it pays particular attention on the context of micro and small enterprises (MSEs) in resource-constrained environments – a common feature of most emerging economies. Knowledge about the underlying factors that determine bricolage as a common practice among MSEs operating in emerging economies is yet to advance and develop within the mainstream entrepreneurship literature. Much of this scholarship tends to focus on multi-national enterprises (MNEs) in advanced economies and it discusses bricolage as their strategic choice. Such an approach has led to a lack of meaningful theoretical paradigms for defining the business approaches MSEs adopt as a way of mitigating their perennial operational issues inherent in their environment. Thus, in this conceptual paper, which adopts a scoping review approach, we study the constructs of bricolage particularly their application in MSEs operating in emerging economies. From our analysis a fresh deterministic model mapping out the causal factors that give rise to bricolage behaviour in MSEs that operate in difficult conditions emerged. Thus, we contribute to entrepreneurial behaviour theories by identifying distinctive business methods MSEs adopt to withstand operational difficulties inherent in their environments.